Boundary Value Problems for a Super-Sublinear Asymmetric Oscillator: The Exact Number of Solutions - Armands Gritsans; Felix Sadyrbaev (International Journal of Mathematics and Mathematical Sciences)
Properties of asymmetric oscillator described by the equation (i), where and , are studied. A set of such that the problem (i), (ii), and (iii) have a nontrivial solution, is called α-spectrum. We give full description of α-spectra in terms of solution sets and solution surfaces. The exact number of nontrivial solutions of the two-parameter Dirichlet boundary value problem (i), and (ii) is given.